Actinotignum schaalii subcutaneous abscesses in a patient with hidradenitis suppurativa: Case report and literature review. (February 2017) - Maraki, Sofia; Evangelou, George; Stafylaki, Dimitra; Scoulica, Efstathia
Abstract: Actinotignum schaalii (formerly Actinobaculum schaalii) is a Gram-positive, facultative anaerobic rod that is typically involved in urinary tract infections in elderly patients or those with underlying urological pathologies. In contrast, abscess formation caused by A. schaalii is very rare. We present a case of multiple abscesses in the perineal area in a young patient with hidradenitis suppurativa associated with A. schaalii and Prevotella melaninogenica and review the relevant literature on the topic. Highlights: We report a case of Actinotignum schaalii related abscesses in a patient with hidradenitis suppurativa. A. schaalii was identified using Vitek 2 ANC identification cards and 16S rRNA sequencing. The patient was successfully treated with a combination of surgical drainage, antibiotics and TNF inhibitor. A. schaalii is an underestimated pathogen because of its fastidious growth and challenging identification. The literature was reviewed on abscesses caused by A. schaalii.